Association between probable postnatal depression and increased infant mortality and morbidity: findings from the DON population-based cohort study in rural Ghana. Issue 8 (27th August 2015) - Weobong, Benedict; ten Asbroek, Augustinus H A; Soremekun, Seyi; Gram, Lu; Amenga-Etego, Seeba; Danso, Samuel; Owusu-Agyei, Seth; Prince, Martin; Kirkwood, Betty R
Abstract : Objectives: To assess the impact of probable depression in the immediate postnatal period on subsequent infant mortality and morbidity. Design: Cohort study nested within 4 weekly surveillance of all women of reproductive age to identify pregnancies and collect data on births and deaths. Setting: Rural/periurban communities within the Kintampo Health Research Centre study area of the Brong-Ahafo Region of Ghana. Participants: 16 560 mothers who had a live singleton birth reported between 24 March 2008 and 11 July 2009, who were screened for probable postnatal depression (pPND) between 4 and 12 weeks post partum (some of whom had also had depression assessed at pregnancy), and whose infants survived to this point. Primary/secondary outcome measures: All-cause early infant mortality expressed per 1000 infant-months of follow-up from the time of postnatal assessment to 6 months of age. The secondary outcomes were (1) all-cause infant mortality from the time of postnatal assessment to 12 months of age and (2) reported infant morbidity from the time of the postnatal assessment to 12 months of age. Results: 130 infant deaths were recorded and singletons were followed for 67 457.4 infant-months from the time of their mothers' postnatal depression assessment. pPND was associated with an almost threefold increased risk of mortality up to 6 months (adjusted rate ratio (RR), 2.86 (1.58 to 5.19); p=0.001). The RR up to 12 months was 1.88 (1.09 to 3.24; p=0.023). pPND was also associated with increased risk of infant morbidity. Conclusions: There is new evidence for the association between maternal pPND and infant mortality in low-income and middle-income countries. Implementation of the WHO's Mental Health Gap Action Programme (mhGAP) to scale up packages of care integrated with maternal health is encouraged as an important adjunct to child survival efforts.